REDUCTION OF WEIGHT GAIN AND MORTALITY CAUSED BY DIARRHEA IN SUCKLING PIGLETS - TAGLIARI, KELLY CRISTINA (1998)
Diarrhea problems are frequent in suckling piglets, but the extent of associated losses generally is not reported. The present work discusses the occurrence of diarrhea, weight gain reduction and their effects on piglet mortality in a pig farm. Diarrhea was present in 48,6% among 210 liters analyzed. There was a reduction in weight gain of 21 %, 20%, 14% and 09%, on first, second, third and fourth week of life, respectively. Diarrhea caused a mortality rate of 0,79% among the piglets bom in the period.